2016
DOI: 10.1139/cjfas-2015-0460
|View full text |Cite
|
Sign up to set email alerts
|

TheCladophoraresurgence in Lake Ontario: characterization and implications for management

Abstract: Nuisance growth of the alga Cladophora, reported from Lake Ontario since the 1930s, abated in the decades following implementation of phosphorus control measures in the 1970s. Our examination of beach fouling records and historical observations of algal biomass has confirmed literature reports that a resurgence in nuisance growth of Cladophora has occurred since invasion of Great Lakes waters by dreissenids. Our findings indicate that the growth rate of Cladophora (specific rate of net photosynthesis) has decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…External loading of TIN should be more evident compared to SRP because of the proportionally lower biological utilization of the total supply. Unlike phosphorus, TIN concentrations are thought to remain above growth-limiting levels for phytoplankton (e.g., [45]) and Cladophora [9,18]. Linear regressions predicting SRP and TP from TIN were significant for three and two of seven sampling events, respectively ( Table 7), suggesting that lakebed TIN may be a predicator of external loading of phosphorus, such as in August 2012, but that this is not consistently the case.…”
Section: Nearbed Concentrations Of Dissolved Nutrients To Detect Enrimentioning
confidence: 99%
See 2 more Smart Citations
“…External loading of TIN should be more evident compared to SRP because of the proportionally lower biological utilization of the total supply. Unlike phosphorus, TIN concentrations are thought to remain above growth-limiting levels for phytoplankton (e.g., [45]) and Cladophora [9,18]. Linear regressions predicting SRP and TP from TIN were significant for three and two of seven sampling events, respectively ( Table 7), suggesting that lakebed TIN may be a predicator of external loading of phosphorus, such as in August 2012, but that this is not consistently the case.…”
Section: Nearbed Concentrations Of Dissolved Nutrients To Detect Enrimentioning
confidence: 99%
“…A key factor in the resurgence in Cladophora, previously a problem in the 1960-1980s when the lake was more nutrient enriched, is the improved light climate of the lake following the invasion of dreissenid mussels [16] in about 1990 [17]. Kuczynski et al [18] have convincingly demonstrated that there has indeed been a resurgence in Cladophora which can be directly attributed to the changing light climate. These studies have concluded that the growth potential for Cladophora has increased markedly compared with the period prior to the deepening photic zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the invasion of zebra mussels ( Dreissena polymorpha ) and quagga mussels ( Dreissena bugensis ) in the late 1980s amplified the expansion of Cladophora through a cascade of interrelated ecological processes. These influences include increased water clarity, which expanded algal growth conditions to deeper waters; availability of additional substrates (e.g., mussel beds) for attachment and growth; and nutrient capture and regeneration (e.g., phosphorus) (Auer et al, ; Davies & Hecky, ; Higgins, Pennuto, Howell, Lewis, & Makarewicz, ; Kuczynski, Auer, Brooks, & Grimm, ) (see Figure , left panel). Phosphorus is recognized as the limiting nutrient for Cladophora growth in the Great Lakes (Auer & Canale, ; Higgins et al, ), and phosphorus cycling by dreissenid mussels in benthic areas (e.g., via pseudofeces, inorganic excretion) (Nalepa, Gardner, & Malczyk, ) is believed to have played an important role in Cladophora expansion post‐mussel invasion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the invasion of zebra mussels (Dreissena polymorpha) and quagga mussels (Dreissena bugensis) in the late 1980s amplified the expansion of Cladophora through a cascade of interrelated ecological processes. These influences include increased water clarity, which expanded algal growth conditions to deeper waters; availability of additional substrates (e.g., mussel beds) for attachment and growth; and nutrient capture and regeneration (e.g., phosphorus) (Auer et al, 2010;Davies & Hecky, 2005;Higgins, Pennuto, Howell, Lewis, & Makarewicz, 2012;Kuczynski, Auer, Brooks, & Grimm, 2016) (see Figure 1, left panel).…”
Section: Introductionmentioning
confidence: 99%